Kepemimpinan Transformasional, Spiritual, dan Distributif Berbasis Tauhid: Sintesis Model Islami untuk Pendidikan Abad 21 - Lia Herliawati; Ika Kartika; Noor Albar; Koko Abdul Mutolib; Hiyarul Umam (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This article presents a conceptual synthesis of three leadership models—transformational, spiritual, and distributive—within the framework of tauhid as an Islamic leadership approach relevant to 21st-century education. Tauhid is positioned as an epistemological foundation that guides leadership practices toward prophetic vision, transcendental awareness, and collective participation. Through a systematic literature review, this study demonstrates that integrating these models effectively addresses the challenges of digitalization, religious moderation, and character development among Muslim Generation Z. The synthesis not only strengthens the philosophical basis of Islamic educational leadership but also offers practical implications for curriculum design, leadership training, and institutional management grounded in tauhid values.